2018
DOI: 10.1016/j.jconrel.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic activated ester prodrug approach for drug delivery to the intestinal lymphatic system

Abstract: The intestinal lymphatic system plays an important role in the pathophysiology of multiple diseases including lymphomas, cancer metastasis, autoimmune diseases, and human immunodeficiency virus (HIV) infection. It is thus an important compartment for delivery of drugs in order to treat diseases associated with the lymphatic system. Lipophilic prodrug approaches have been used in the past to take advantage of the intestinal lymphatic transport processes to deliver drugs to the intestinal lymphatics. Most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Stability of cordycepin in plasma was tested using human and rat plasma by following a previously reported method with minor modifications 44 . Cordycepin was spiked into the plasma at 10 µM and the samples were incubated in a shaking incubator (Thermo Scientific MaxQ4000, Waltham, MA, USA) at 37 °C and shaken at 250 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Stability of cordycepin in plasma was tested using human and rat plasma by following a previously reported method with minor modifications 44 . Cordycepin was spiked into the plasma at 10 µM and the samples were incubated in a shaking incubator (Thermo Scientific MaxQ4000, Waltham, MA, USA) at 37 °C and shaken at 250 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously suggested that it is the inherent physicochemical properties of the drug that determines the association ability of the drug with chylomicrons which eventually governs intestinal lymphatic transport 17,31 . The intestinal lymphatic transport of BEX, with its low chylomicron association reported previously 32 , was not affected by LBDDS. It confirms the relevance of application of liver microsomal stability in bioavailability prediction as minimal lymphatic transport would mean that hepatic first-pass effect would be applied to BEX 8 .…”
Section: Discussionmentioning
confidence: 49%
“…In this study, we assessed the intestinal lymphatic transport potential of TU by measuring the association with plasma-derived human CM. This approach was previously shown to provide accurate estimate for the intestinal lymphatic transport of lipophilic compounds [ 18 , 21 , 28 ]. The high association value of TU with CM in this study (84.3%) suggests considerable intestinal lymphatic transport and improved bioavailability following oral administration in conditions that promote CM assembly, particularly with long-chain triglyceride-rich lipids.…”
Section: Discussionmentioning
confidence: 99%
“…FaSSIF was prepared according to the literature [ 17 ]. The stability of TU in FaSSIF/ES was performed as described in the literature [ 18 , 19 ]. The reaction medium (1 mL) was incubated at 37 °C for 5 min prior to the experiment.…”
Section: Methodsmentioning
confidence: 99%